Design Thinking Strategy On Improving Academic Administration Bureau Services (Case Study: Bakrie University) - Chairani, Metha Erzha; Arief Bimantoro Suharko (Jurnal Scientia, 2024)
This research discusses the application of design thinking strategies in improving services at the Academic Administration Bureau of Bakrie University. Design thinking, as an approach that focuses on a deep understanding of user needs, was adapted to identify and address challenges faced in academic administration services. Through a qualitative method involving observation, interviews, and documentation analysis, this study found that design thinking can improve the service process by socializing with students to integrate user perspectives and increase student satisfaction. This research concluded that design thinking can be used to improve Bakrie University services by socializing to stakeholders about services so that a target of 90% of active students at Bakrie University understand existing services is obtained. The results of implementing this strategy show an increase in service quality, as well as providing valuable insights for the development of academic administration services in higher education.